Polyphenol-Rich Extracts from Cotoneaster Leaves Inhibit Pro-Inflammatory Enzymes and Protect Human Plasma Components against Oxidative Stress In Vitro - Kicel, Agnieszka (Molecules, 2018)
The present study investigated the phenolic profile and biological activity of dry extracts from leaves of C. bullatus, C. zabelii and C. integerrimus—traditional medicinal and dietary plants—and evaluated their potential in adjunctive therapy of cardiovascular diseases. Complementary UHPLC-PDA-ESI-MS(3), HPLC-PDA-fingerprint, Folin-Ciocalteu, and n-butanol/HCl assays of the extracts derived by fractionated extraction confirmed that they are rich in structurally diverse polyphenols (47 analytes, content up to 650.8 mg GAE/g dw) with proanthocyanidins (83.3–358.2 mg CYE/g) dominating in C. bullatus and C. zabelii, and flavonoids (53.4–147.8 mg/g) in C. integerrimus. In chemical in vitro tests of pro-inflammatory enzymes (lipoxygenase, hyaluronidase) inhibition and antioxidant activity (DPPH, FRAP), the extracts effects were dose-, phenolic- and extraction solvent-dependent. The most promising polyphenolic extracts were demonstrated to be effective antioxidants in a biological model of human blood plasma—at in vivo-relevant levels (1–5 µg/mL) they normalized/enhanced the non-enzymatic antioxidant capacity of plasma and effectively prevented peroxynitrite-induced oxidative/nitrative damage of plasma proteins and lipids. As demonstrated in cytotoxicity tests, the extracts were safe—they did not affect viability of human peripheral blood mononuclear cells. In conclusion, Cotoneaster leaves may be useful in development of natural-based products, supporting the treatment of oxidative stress/inflammation-related chronic diseases, including cardiovascular disorders.